Aktualisasi Nilai Juang : Keterlibatan Pemuda Panca Marga dalam Peringatan HUT Tentara Nasional Indonesia (TNI) Tahun 2025 (Suatu Bentuk Eksistensi) - Mecky Pirsouw; Andika Gatot Setiawan; Asep Saepudin; Maudhy Satyadharma; Tina Trisarana Andriani Silondae (Indo Publishing, 2025)
PPM as a direct descendant of veteran independence fighters has a moral responsibility to continue the values ​​of patriotism, loyalty, and the spirit of defending the country. Through active participation in ceremonies and parades, PPM demonstrates its contribution in strengthening national identity, character education, and the existence of national organizations in the public sphere. This study discusses the involvement of Pemuda Panca Marga (PPM) in the commemoration of the 80th anniversary of the Indonesian National Armed Forces in 2025 as a form of actualization of the values ​​of struggle and the existence of the organization. This study uses a qualitative descriptive approach to describe the symbolic and strategic impact of PPM's presence in state moments. The study found that PPM's contribution to the TNI Anniversary Commemoration Activities was in the form of participating in the Parade and following the ceremonial line. Meanwhile, the impact of this involvement is that PPM affirms national identity, PPM contributes to encouraging character education and demonstrates its existence as a national organization and the Extended Family of the Army (KBT).